Analisa dan Perancangan Sistem Informasi Geografis dan Manajemen Aset PT. X - Singadji, Marcello; Evi, Tiolina (JIK: Jurnal Ilmu Komputer, 2013)
The third millennium is marked by rapid advancement of technological development is very fast in all areas, therefore people in this world began working to create new innovations in order to support its activities a day - which in recent hari.Teknologi developing very rapidly and become a worldwide concern is the development of Information Technology (IT) which is a combination of Computer Technology and Communication Technology.With this technology, more and more organizations or companies who started to use and exploit information technology to conduct its business as it is more effective and efficient than the magnitude of the costs if done manually. Transitional or developing an existing system, expected to occur perubahanataupeningkatan so the results are more optimal performance because the error rate would be reduced drastically.Planning a systematic and mature from an activity is a basic characteristic of modern industry, because basically effective planning of materials, machinery, and money will be towards the acquisition of profit is so important in a company. Along with the development of an enterprise is to face the above mentioned factors should be considered a material planning system that can support the production of all production activities as one step in the process of decision making. PT X is an object that is taken because it is considered as one business unitwho always want improvement and progress in his ministry and his own business. Along with the development of technology, many problems that occur relating to the implementation of asset management systems in PT. X.Keywords: analysis, design, information systems